IMPLEMENTASI METODE AGILE DAN FRAMEWORK LARAVEL PADA PENGEMBANGAN SISTEM INFORMASI BIMBINGAN SKRIPSI BERBASIS WEB - Rahman Rahman; Niswa Ayu Lestari; Hastuti Hastuti (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
The rapid development of web technology can be used to automate various processes, including thesis guidance. The thesis guidance process in the Information Systems Study Program, Faculty of Science and Technology, is currently carried out by students coming directly to the supervisor by bringing printed documents. In the meeting, the lecturer provides revision points through a consultation sheet. However, this method has limited access to the results of the guidance and also has a negative impact on the environment. To overcome this obstacle, this study proposes the development of a